2011
DOI: 10.1186/1471-2431-11-62
|View full text |Cite
|
Sign up to set email alerts
|

Brain iron accumulation in unexplained fetal and infant death victims with smoker mothers-The possible involvement of maternal methemoglobinemia

Abstract: BackgroundIron is involved in important vital functions as an essential component of the oxygen-transporting heme mechanism. In this study we aimed to evaluate whether oxidative metabolites from maternal cigarette smoke could affect iron homeostasis in the brain of victims of sudden unexplained fetal and infant death, maybe through the induction of maternal hemoglobin damage, such as in case of methemoglobinemia.MethodsHistochemical investigations by Prussian blue reaction were made on brain nonheme ferric iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
(47 reference statements)
2
8
0
Order By: Relevance
“…The conducted proper research found that neonatal jaundice incidence (p=0.034), heart murmur at a later age (p=0.011) and mild disorders in children and adults such as dyslalia and learning/memory impairments (p=0.002) were significantly higher than in children and adults of control mothers without pregnancy methemoglobinemia [17]. Lavezzi AM, Mohorovic L, et al recently presented the findings confirmed by pathohistological technique that under the adverse conditions, ferric iron positivity in capillary endothelial cells of the blood-brain barrier in the fetus rises, also resulting in preterm birth, stillbirth or early neonatal death [18]. The application of the Blue Prussian method highlighted the accumulations of blue granulations, indicative for non-heme Fe 3+ positive reactions, in the brainstem and cerebellum of 12 (33%) of the 36 victims, while there were none in the control group.…”
Section: Resultssupporting
confidence: 61%
“…The conducted proper research found that neonatal jaundice incidence (p=0.034), heart murmur at a later age (p=0.011) and mild disorders in children and adults such as dyslalia and learning/memory impairments (p=0.002) were significantly higher than in children and adults of control mothers without pregnancy methemoglobinemia [17]. Lavezzi AM, Mohorovic L, et al recently presented the findings confirmed by pathohistological technique that under the adverse conditions, ferric iron positivity in capillary endothelial cells of the blood-brain barrier in the fetus rises, also resulting in preterm birth, stillbirth or early neonatal death [18]. The application of the Blue Prussian method highlighted the accumulations of blue granulations, indicative for non-heme Fe 3+ positive reactions, in the brainstem and cerebellum of 12 (33%) of the 36 victims, while there were none in the control group.…”
Section: Resultssupporting
confidence: 61%
“…Obtained proper research found an incidence of neonatal jaundice (p = 0.034), heart murmur at a later age (p = 0.011), as well as child and adult mild disorders such as dyslalia and learning/memory impairments (p = 0.002) significantly higher than in the children and adults of control mothers without pregnancy methemoglobinemia [12]. Lavezzi, Mohorovic et al recently presented findings, confirmed by pathohistological techniques, that under adverse conditions, ferric iron positivity in capillary endothelial cells of the BBB in the fetus rises, also resulting in preterm birth, stillbirth or early neonatal death [13]. The application of the Blue Prussian method highlighted accumulations of blue gra-nulations, indicative of nonheme Fe 3+ -positive reactions in the brainstem and cerebellum of 12 (33%) of the 36 sudden intrauterine unexplained death (SIUD) and sudden infant death syndrome (SIDS) victims and in none of the control group.…”
Section: Methods and Resultsmentioning
confidence: 58%
“…The positivity of free iron in the cerebral parenchyma of a patient with Alzheimer's disease is represented in Figure 6. In the same cases of their previous study [13], Lavezzi, Mohorovic et al, by applying the TUNEL method, highlighted in the same cases showing iron deposition in the capillary endothelial cells of the BBB and in the brain parenchima, high percentages of apoptotic cells in the ventricular barriers, and precisely in the ependyma and in choroid plexus epithelial cells (Figures 7 and 8). …”
Section: Methods and Resultsmentioning
confidence: 60%
“…Other staining materials are Lillie for the neuromelanin pigment (28) and Perl’s Prussian blue for iron in oxygen-transporting heme mechanism (29). …”
Section: Stepwise Proceduresmentioning
confidence: 99%